Frequency of Isolated Ocular Motor Nerves Palsy in Patients with Multiple Sclerosis in Isfahan, Iran - Hassan Razmju; Masoud Etemadifar; Zahra Abtahi; Mohammad-Ali Abtahi; Seyed-Hossein Abtahi (مجله دانشکده پزشکی اصفهان, 2011)
Background: Ocular motor disturbances occur as the presenting or relapsing sign/symptom of multiple sclerosis (MS). In this study we sought to asses the frequency of isolated ocular motor nerves palsy in patients with in Isfahan, Iran. Methods: Our study was a retrospective study on 3522 patients with definite MS (based on McDonald’s criteria), who had experienced isolated ocular motor nerves palsy as a presenting or relapsing sign. All of these patients were resident within Isfahan province until the end of July 2010 and they were registered in Isfahan MS society. Data were obtained retrospectively by analyzing patients’ regular follow-up records. Finding: 76 patients (2.15) had history of isolated ocular motor nerves palsy, in whom 32 cases (0.91%) and 44 cases (1.24%) had represented it “at the onset” and “during the course” of MS, respectively (P = 0.19). Abducens nerve palsy was seen in 56 patients (1.59%) and was the most common isolated ocular motor nerves palsy. The second prevailing palsy was pertaining to oculomotor nerve which was seen in 18 patients (0.51%). The least prevailing palsy was of Trochlear nerve that occurred in 2 patients (2.6%). Among 76 cases, only 30 had plaques in their brainstem MRI. Conclusion: According to our current experience, the frequency of isolated ocular motor nerves palsy (2.15%) in MS is relatively low.